Sonogashira cross-coupling reactions of 3, 5-dibromo-2, 6-dichloropyridine. Issue 6 (24th January 2017) - Reimann, Sebastian; Ehlers, Peter; Ohlendorf, Lars; Langer, Peter
Abstract : Polyalkynylated pyridines were obtained by chemoselective Sonogashira reactions which are not accessible by other methods. Abstract : A new method for the chemoselective synthesis of alkynylpyridines from 3, 5-dibromo-2, 6-dichloropyridine has been developed. Optimized conditions give access to a variety of mono-, di-, tri- and tetraalkynylated pyridines in good yields. Interestingly, the employment of 3, 5-dibromo-2, 6-dichloropyridine as a starting material led to the opposite regioisomers of dialkynylated pyridines as compared to the application of 2, 3, 5, 6-tetrachloropyridine.